Impact of process misconception in Becker-Degroot-Marschak single response value elicitation procedures: An experimental investigation in consumer behavior using the IKEA effect - Carolyn Predmore; Kudret Topyan; Lauren Trabold Apadula (Economies, 2021)
Consumer researchers frequently employ valuation experiments to assess consumer opinions and test related hypotheses. One popular method used in many such experiments is the Becker-DeGroot-Marschak (BDM) single-response value elicitation procedure that initiates an incentive for the subjects to respond with their true valuation by utilizing a random bid to which the participants' bid is compared. However, the "random bid" is not a straightforward concept, and the participants may not fully understand the mechanics of the bidding process. Therefore, they may incorrectly associate the bidding mechanism with a conventional auction bidding process in which the highest bidder wins, causing biased valuation outcomes. In this paper, we introduce a comprehension measurement step to eliminate the process comprehension bias in BDM valuation experiments. We also discuss the potential impact of the treatment of "zero" bidders in the BDM procedure. The present work shows that the size and statistical significance of past consumer research results are positively correlated with the participant comprehension of the valuation procedure. The results suggest that consumer research using a single-response value elicitation procedure, which initiates an incentive for the subjects to respond with their true valuation, may not be trusted if the comprehension level is not controlled.
Keywords: 330; BDM auctions; pricing experiments; subject misconception; true valuation